Interferon‐inducible cholesterol‐25‐hydroxylase restricts hepatitis C virus replication through blockage of membranous web formation. Issue 3 (28th July 2015) - Anggakusuma; Romero‐Brey, Inés; Berger, Carola; Colpitts, Che C.; Boldanova, Tujana; Engelmann, Michael; Todt, Daniel; Perin, Paula Monteiro; Behrendt, Patrick; Vondran, Florian W.R.; Xu, Shuting; Goffinet, Christine; et al.
<x xml:space="preserve">Abstract</x> Hepatitis C virus (HCV) is a positive‐strand RNA virus that primarily infects human hepatocytes. Infections with HCV constitute a global health problem, with 180 million people currently chronically infected. Recent studies have reported that cholesterol 25‐hydroxylase (CH25H) is expressed as an interferon‐stimulated gene and mediates antiviral activities against different enveloped viruses through the production of 25‐hydroxycholesterol (25HC). However, the intrinsic regulation of human CH25H (hCH25H) expression within the liver as well as its mechanistic effects on HCV infectivity remain elusive. In this study, we characterized the expression of hCH25H using liver biopsies and primary human hepatocytes. In addition, the antiviral properties of this protein and its enzymatic product, 25HC, were further characterized against HCV in tissue culture. Levels of hCH25H messenger RNA were significantly up‐regulated both in HCV‐positive liver biopsies and in HCV‐infected primary human hepatocytes. The expression of hCH25H in primary human hepatocytes was primarily and transiently induced by type I interferon. Transient expression of hCH25H in human hepatoma cells restricted HCV infection in a genotype‐independent manner. This inhibition required the enzymatic activity of CH25H. We observed an inhibition of viral membrane fusion during the entry process by 25HC, which was not due to a virucidal effect. Yet the primary effect by 25HC on HCV was at the level of RNA replication, which was observed using subgenomic replicons of two different genotypes. Further analysis using electron microscopy revealed that 25HC inhibited formation of the membranous web, the HCV replication factory, independent of RNA replication. Conclusion: Infection with HCV causes up‐regulation of interferon‐inducible CH25H in vivo, and its product, 25HC, restricts HCV primarily at the level of RNA replication by preventing formation of the viral replication factory. (Hepatology 2015;62:702–714)